Personalized medicine in gynecology and obstetrics: new diagnostic and therapeutic strategies - A. D. Makatsariya; A. V. Vorobev (Акушерство, гинекология и репродукция)
This journal issue presents studies in the field of obstetrics, gynecology and reproductive medicine. The original articles consider the genetic aspects of preeclampsia, including the role of NOS3 gene rs1799983 polymorphism, modern approaches for predicting uterine fibroids using neural network technologies, and vasopressin value as a marker of premature birth. Particular attention is paid to personalized methods of treating coagulopathic bleeding based on thromboelastometry and pregnancy management in chronic kidney pathology. The review articles analyze the pharmacological properties of iron fumarate, the role of the ARID1A gene in gynecological oncology, microbiome impact on the effectiveness of assisted reproductive technologies and the pathogenesis of fetal inflammatory syndrome. Clinical observation describes a rare case of spontaneous uterine rupture, and a historical analysis of forgotten obstetric techniques is presented.